Adaptive sliding mode control for stochastic switched systems with actuator faults. (April 2019) - Liu, Yonghui
The problem of adaptive sliding mode control is considered for a class of stochastic switched systems with actuator degradation. In this work, the input matrix for each subsystem is unnecessarily the same. Thus, a weighted sum approach of the input matrices is introduced such that a common sliding surface is designed. By online estimating the loss of effectiveness of the actuators, an adaptive sliding mode controller is designed. It can not only compensate the effect of the actuator degradation effectively, but also reduce the conservatism that the bound of the actuator faults should be known in advance. Moreover, it is shown that the reachability of the sliding surface can be guaranteed. Furthermore, sufficient conditions on the mean-square exponential stability of the sliding mode dynamics are obtained via the average dwell time method. Finally, a numerical simulation example is given to demonstrate the effectiveness of the proposed method.